The Effect of Cement and wrapping on the Decomposition rate of the Rabbit Carcasses - Lai Poh Soon; Khoo Lay See; Nazni Wasi Ahmad; Azlina Zulkapli; Nurul Kharmila Abdullah; Mohd Shah Mahmood; Ahmad Hafizam Hasmi (Heighten Science Publications Corporation, 2024)
Non-Indexed Publication